The Effects of Progesterone on Hypoxic Ischemic Injuries in the Cornu Ammonis (CA) Region of the Hippocampus of Neonatal Rats - Khan, A.A; Norhida, Binti Ramli; Zulizhar, Mohd. Ismail (SciELO, 2015)
Hypoxia-ischemia (HI) is a major cause of brain damage in the newborn. Several studies elicited the neuroprotective effects of progesterone in adult rats but there is very little literature available on neonatal rats. Therefore the present study is undertaken to see the effect of progesterone in hypoxic ischemic brain injury in neonatal rats, using an established neonatal HI rat pup model. Sevenday- old rat pups were subjected to right common carotid artery ligation and then 60 minutes hypoxia. The first dose of progesterone to treatment group was administered by peritoneal injection (4 mg/kg), after 10 minutes of exposure and subsequent doses were given by subcutaneous injection at 6 h, 24 h and 48 h intervals. Control group was also exposed to HI and was given only the vehicle (peanut oil) through the same route and intervals as that of treatment group. After 96 h, the pups were perfused with 10% formalin and brains were sampled and stained with toluidine blue. Cells density and number of pyramidal cells of the hippocampal Cornu Ammonis (CA) regions were examined by stereological methods. The histomorphometric assessment of the effects of progesterone showed minimal but no significant protective value in the volume, cells density and total number of pyramidal cells of hippocampal CA region of the treatment and control groups (p>0.05) after HI. Our results concluded that 4 mg/kg of PROG had no significant neuroprotective effect in HI model of the neonatal rat’s hippocampus.